(untitled) (Research, Society and Development, 2022)
Breastfeeding is one of the great and important events in the first months of a baby’s life. The World Health Organization recommends that breastfeeding (BF) be done exclusively until the baby’s sixth month of life. After that age, food introduction (AI) should be done correctly, gradually and slowly, together with breastfeeding, preferably until the age of two. AI can be performed in different ways, such as: traditional, participatory and Baby Led Weaning (BLW). The objective of this study was to seek information on food introduction, analyzing the relationship between breastfeeding and diseases and allergies with erroneous and early food introduction in children and demonstrating the importance of exclusive breastfeeding until the sixth month of life. This is a bibliographic review study using scientific articles and books on the subject in Portuguese languages, using data carried out in specialized centers: Scielo, Lilacs, Pubmed, between 2009 and 2022. Exclusive BF up to six months of age , and AI is extremely important for the child to have adequate growth, avoiding the emergence of diseases and food allergies, childhood obesity and even in adulthood, in addition, there are studies linking breastfeeding to the development of the child’s intelligence.